1,1?-Bis(3-methyl-3-phenylcyclobutyl)-2,2?-(azanediyl) diethanol - Sen, Fatih; Dincer, Muharrem; Cukurovali, Alaaddin; Yilmaz, Ibrahim (Int Union Crystallography, 2012)
The title molecule, C26H35NO2, contains two cyclobutane rings that adopt butterfly conformations and are linked by a -CH(OH) CH2NHCH2CH(OH)- bridge. In the crystal, N-H center dot center dot center dot O, O-H center dot center dot center dot N and O-H center dot center dot center dot O hydrogen bonds together with C-H center dot center dot center dot pi interactions link the molecules.